The Effect of Chronic Energy Deficiency on the Incidence of Stunting in Childern Aged 24-59 Months - Nisa Khoirotul Qoni'ah; Astuti Setiyani; Nurlailis Saadah; Sulikah Sulikah (International Journal of Advanced Health Science and Technology, 2026)
Chronic Energy Deficiency (CED) during pregnancy is a significant public health concern with long-term effects on maternal and child health. The study explores the impact of maternal CED on stunting in children aged 24-59 months in Ngariboyo Public Health Center, where the prevalence of CED among pregnant women was 11.01% in 2023, and stunting affected 8.2% of children. The primary aim of this study is to determine the relationship between maternal CED and the incidence of stunting in the target population. Employing an analytical observational approach, this case-control study included 32 children with stunting as the case group and 64 non-stunted children as the control group, selected through random sampling methods. Data on maternal CED were obtained from maternal and child health records, while stunting data were gathered via questionnaires. The analysis utilized chi-square and Mantel-Haenszel common odds ratio tests to evaluate the association. The results indicated a significant association (p=0.021) between maternal CED and stunting, with an odds ratio of 3.201, suggesting that mothers with CED have a 3.2 times higher risk of giving birth to stunted children compared to mothers without CED. The study concludes that maternal CED is a crucial factor contributing to stunting in children. Therefore, interventionssuch as early identification and nutritional education for pregnant women are essential for stunting prevention. The findings emphasize the need for targeted public health policies to address maternal nutrition in rural settings.